Dual oxidase‐dependent reactive oxygen species are involved in the regulation of UGT overexpression‐mediated clothianidin resistance in the brown planthopper, Nilaparvata lugens. Issue 9 (14th May 2021) - Zhang, Yunhua; Liu, Chaoya; Jin, Ruoheng; Wang, Yue; Cai, Tingwei; Ren, Zhijie; Ma, Kangsheng; He, Shun; Lee, Kwang S; Jin, Byung R; Li, Jianhong; Wan, Hu
Abstract: BACKGROUND: Uridine diphosphate‐glycosyltransferases (UGTs) are phase II metabolic enzymes involved in metabolism of toxins and resistance to insecticides in insect pests. Reactive oxygen species (ROS) induced by xenobiotics are important for activation of detoxification pathways. However, relationships between ROS and UGTs involved in toxin metabolism and insecticide resistance remain unclear. RESULTS: Here, involvement of dual oxidase (Duox)‐dependent ROS in regulating UGT expression‐mediated insecticide resistance in the brown planthopper ( Nilaparvata lugens ) was investigated. The overexpression of NlUGT386F2 contributed to the resistance of N. lugens to clothianidin. Furthermore, the ROS inhibitor ( N ‐acetylcysteine) significantly reduced the expression of NlUGT386F2 and increased the susceptibility of N. lugens to clothianidin. Silencing the ROS producer Duox significantly increased the susceptibility of N. lugens to clothianidin through the down‐regulation of NlUGT386F2 expression. CONCLUSION: NlDuox‐ dependent ROS regulates NlUGT386F2 expression‐mediated clothianidin resistance in brown planthopper. These observations further our understanding of the metabolism of toxins and of insecticide‐resistance in insect pests. Abstract : Dual oxidase dependent reactive oxygen species (ROS) regulates NlUGT386F2 expression. Overexpression of NlUGT386F2 contributes to clothianidin resistance. ROS reduction can decrease clothianidin resistance via reducing NlUGT386F2 expression. © 2021 Society of Chemical Industry.